(untitled) - Wilmerding, Ginny (New Jersey, 2006)
The goal of this book is to get you started on the path to a successful career in the small business world, a world that needs experienced, smart, versatile women like you to join its ranks. Smart Women and Small Business is the ultimate professional guide for mid-career, business-minded women who want to achieve the same independence and success as their entrepreneurial male peers—but in their own way
Keywords: Self-employed women,Businesswomen,Women-owned business enterprises,Vocational guidance of women,Phụ nữ làm chủ,Nữ doanh nhân,Phụ nữ làm chủ doanh nghiệp kinh doanh,Hướng dẫn dạy nghề của phụ nữ; United States,United States,United States,United States,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ